การศึกษาความสัมพันธ์เชิงสาเหตุของการรับรู้ชุมชนแห่งการเรียนรู้ทางวิชาชีพ จรรยาบรรณความเป็นครู ที่ส่งผลต่อการรับรู้ความสามารถด้านการสอน ของนักศึกษาฝึกประสบการณ์วิชาชีพครู - เอราวรรณ์, วราพร (Journal of Research and Curriculum Development, 2020)
The objectives of this research were to 1) study causal relationship between Teachers’ Perception of Professional Learning Community, the Teacher’s Code of Ethics and Teaching Efficacy of Pre-Service Teachers 2) examine invariance of causal relationship model between Teachers’ Perception of Professional Learning Community, the Teacher’s Code of Ethics and Teaching Efficacy of Pre-Service Teachers. This was a survey research. Data were collected from 1,337 pre-service teachers who work practice in primary education schools in Thailand by multistate random sampling method. The instruments of this research consist of The Professional Learning Community scale, the Teaching Efficacy scale and the Teacher Ethics scale. The data were analyzed by Frequency distribution, Percentage, Mean, Standard Deviation, Correlation Analysis, and Structural Equation Model Analysis with Mplus 8.3. The results revealed that 1) Teachers’ Perception of Professional Learning Community and Teacher’s Code of Ethics had positive direct effect to Teaching Efficacy with .405 and .569 effect size at significant level .01. 2) The causal relationship model between Teachers’ Perception of Professional Learning Community, the Teacher’s Code of Ethics and Teaching Efficacy of Pre-Service Teachers were variance among male and female